Evaluation of performance in the pre-analytical phase of a clinical biochemistry laboratory in a Tertiary Medical College Hospital - Chaudhuri, Sayani; Das, Amitabha; Das, Subir Kumar; Tanmay Saha (Asian Journal of Medical Sciences, 2022)
Background: Pre-analytical phase is the major source of errors in a clinical biochemistry laboratory. Aims and Objectives: The study aims to determine the quality of laboratory performance in the pre-analytical phase using quality indicators (QI) specified by the International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) Working Group on Laboratory Errors and Patient Safety and sigma metric scale for both the inpatient and outpatient samples received in the clinical biochemistry laboratory. Materials and Methods: All samples and requisition forms received in the laboratory were examined before analysis. The percentages of the seven QI were calculated. The frequency, percentage, and defects per million rates of each pre-analytical error were calculated. Sigma value was obtained using an online sigma calculator. The laboratory performance was then categorized by the IFCC-based performance levels and sigma-based values. Results: Out of 30,546 samples received during a period of 6 months, pre-analytical errors occurred in 2.8% of them. The highest number of pre-analytical errors was due to hemolysis (29.9%). The outpatient samples showed a desirable to optimum performance with a good sigma value. There were more errors and lower quality-based performance, in the case of inpatient samples. Errors were highest in September at the start of the study followed by a gradual decrease over the next 5 months. Conclusion: The laboratory performance in the pre-analytical phase was found to be favorable and consistent with the international specifications.